Acute toxicity and impact of sublethal exposure to commonly used surfactants sodium dodecyl sulphate, cetylpyridinium chloride and sodium laureth sulphate on oxidative stress enzymes in oligochaete worm Branchiura sowerbyi (Beddard, 1892). (26th July 2021) - Bhattacharya, Ritwick; Chatterjee, Arnab; Chatterjee, Soumendranath; Saha, Nimai Chandra
Abstract: The current study aimed to determine the detrimental effects of sodium dodecyl sulphate (SDS), cetylpyridinium chloride (CPC), and sodium laureth sulphate (SLES) on survival rate and oxidative stress enzymes in Branchiura sowerbyi (Beddard, 1892). The 96 h LC50  values of SDS, CPC and SLES to Branchiura sowerbyi were estimated to be 8.27, 0.12 and 19.58 mg/L, respectively. Moreover, surfactant toxicity was projected using general threshold survival models (GUTS) in terms of required data sets and fit performance. The result suggested that GUTS‐IT (individual tolerance) model can better predict the survival rate observed in Branchiura sowerbyi for surfactant exposure than the GUTS‐SD (stochastic death) model. Sublethal levels of SDS, CPC and SLES (10% and 30% of the 96 h LC50 value) elicited substantial changes in oxidative stress enzymes over the 14‐day exposure period. Superoxide dismutase (SOD), reduced glutathione (GSH), glutathione S‐transferase (GST) and glutathione peroxidase (GPx) demonstrated a significant increasing trend initially followed by a subsequent declining trend, but the levels of catalase (CAT), as well as malondialdehyde (MDA), increased significantly throughout the periods of exposure. The consequences of SDS, CPC and SLES on Branchiura sowerbyi were evaluated using a correlation matrix, principal component analysis, and integrated biomarker response assessment. These findings suggest that SDS, CPC and SLES exposure detrimentally affect survival rate and alter the levels of oxidative stress enzymes in Branchiura sowerbyi .